Perigraft reaction and incorporation of porcine and bovine pericardial patches. (12th December 2020) - Schlachtenberger, Georg; Doerr, Fabian; Brezina, Annamaria; Menghesha, Hruy; Heldwein, Matthias B; Bennink, Gerardus; Menger, Michael D; Moussavian, Mohammed; Hekmat, Khosro; Wahlers, Thorsten
Abstract: OBJECTIVES: Bovine and porcine pericardial patches are frequently used in cardiothoracic and vascular surgery. There are no guidelines recommending the usage of these patches for particular surgical approaches. However, these 2 materials supposedly possess different properties. The clinical advantage of porcine compared with bovine patches remains controversial. In this experimental study, we analysed the incorporation and vascularization of bovine and porcine pericardial patches during the initial phase after implantation. METHODS: Bovine and porcine pericardial patches were implanted into the dorsal skinfold chamber of C57BL/6 mice ( n  = 8 per group) to study vascularization and inflammation at the implantation site using repetitive intravital fluorescence microscopy over a 14-day period. At the end of the in vivo experiments, CD-31-positive cells were determined to evaluate the vascularization by immunohistochemistry. Furthermore, cell proliferation and apoptosis were analysed immunohistochemically. RESULTS: Implanted bovine patches exhibited an enhanced vascularization, as indicated by a significantly higher number of CD-31-positive cells and micro-vessels (23.2 ± 4.3 vs 16.5 ± 5.8 mm −2 ; P  = 0.001). Furthermore, bovine patches showed a slightly but not significantly higher functional capillary density. Both patches induced a moderate leukocytic inflammatory host tissue response, and neither bovine nor porcine patches significantly affected apoptosis and cell proliferation at the implantation site. CONCLUSIONS: Bovine and porcine pericardial patches are similarly suitable for surgery. Bovine patches exhibited an improved vascularization during the first 14 days after implantation. This may result in a quicker and improved incorporation into the surrounding tissue compared with porcine pericardial patches.